Taktik Utama Kepribadian Covert Aggressive pada Tokoh Prospera Mercury (プロスペラ・マーキュリー) dalam Anime Kidou Senshi Gundam: Suisei no Majo - Jauhari, Tantowi; Andari, Novi (KIRYOKU, 2024)
Aggressiveness is a human behavior necessary for achieving life goals, characterized by both positive and negative traits. One form of negative aggressiveness is covert aggressive. Individuals with a covert aggressive personality tend to be dominant and manipulative. Literature reflects life, as seen in the anime "Kidou Senshi Gundam: Suisei no Majo" through the character Prospera Mercury, who exemplifies covert aggressive personality traits. This study aims to describe the principal tactics of covert aggressive personality exhibited by Prospera Mercury. The analysis is based on George K. Simon's concept of covert aggressive personality. Data for this research was collected using the note-taking technique from dialogues and monologues, and presented in a qualitative descriptive form. The results indicate that Prospera Mercury employs pricipal tactics covert aggressive. There are 48 instances demonstrating the use of covert aggressive principal tactics to achieve desired outcomes and exert control over others. The principal tactics used include seduction, lying, playing the victim role, and minimization. The study concludes that Prospera Mercury effectively uses covert aggressive personality traits to control and manipulate those around her, enabling her to maintain a position of power and manage situations to her own advantage.